SOIL MACROFAUNA AND MESOFAUNA COMMUNITY ON AGRICULTURAL LAND IN PLIKEN VILLAGE, KEMBARAN DISTRICT, BANYUMAS REGENCY - Susanto Susanto (Universitas Muhammadiyah Purwokerto, 2022)
Soil is a habitat for various types of fauna, especially macrofauna and soil mesofauna. In general, fertile soil can be found on land used for agricultural activities. The purpose of this study was to determine and reveal the community structure of soil macrofauna and mesofauna which includes individual count, diversity, and dominance as well as environmental quality on agricultural land in Pliken Village, Kembaran District, Banyumas Regency in 2021. The study was carried out in January-June 2021. by using survey method and purposive random sampling technique. Sampling of soil macrofauna and mesofauna was carried out in three locations, namely agricultural land in the west, north, and south of the village. Data sampling was carried out in the morning (07.00-09.00 am) and at night (19.00-21.00 am) 6 times with an interval of once a month. Soil macrofauna and meofuana that had been obtained were identified using the Taxonomy and Identification Key book. An Introduction to the Study of Insects and other references related to the identification of soil macrofauna During the study, 2717 soil macrofauna were found which belong to 15 Orders, 31 Families and 40 Species, while for soil mesofauna, 500 individuals were obtained which belong to 14 Orders, 18 Families. and 21 species.The highest individual count for soil macrofauna came from the Formicideae family (86.86%), while the highest individual count for soil mesofauna came from the Isotomideae family (27%). The index of soil macrofauna diversity on agricultural land in Pliken Village ranged from 0.997- 1,789 with an average of 1,287 which means the level of diversity is moderate, while the index Soil mesofauna diversity ranges from 1.13 to 2.15 with an average of 1.65 which means the level of diversity is moderate. Soil macrofauna dominance index is moderate with a range of 0.264 - 0.546 which indicates that there is still dominance by certain soil macrofauna, namely the Formicideae (ant) family, while the soil mesofauna dominance index ranges from 0.13 to 0.38 with an average of 0.23 which indicates the absence of a predominant species. The environmental quality of agricultural land in Pliken Village is categorized as good to support the life of macrofauna and soil mesofauna. Keywords : Soil Macrofauna, Soil Mesofauna, Individual Count, Diversity, Dominance, Pliken Village Agricultural Land